1998
DOI: 10.1162/evco.1998.6.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Code Growth, Explicitly Defined Introns, and Alternative Selection Schemes

Abstract: Previous work on introns and code growth in genetic programming is expanded on and tested experimentally. Explicitly defined introns are introduced to tree-based representations as an aid to measuring and evaluating intron behavior. Although it is shown that introns do create code growth, they are not its only cause. Removing introns merely decreases the growth rate; it does not eliminate it. By systematically negating various forms of intron behavior, a deeper understanding of the causes of code growth is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Compact solutions are thought to be more robust and generalize better [27,49,61,77,81]. Introns also do seem to provide some protection against the destructive effects of crossover and other genetic operators [1,11,49,70,72] although this may not always be helpful. The usage of explicitly defined artificial introns has yielded generally good results in linear GP [38,50,51], but in tree-based GP it usually degraded the performance of the search process [3,10,70].…”
Section: Bloatmentioning
confidence: 99%
“…Compact solutions are thought to be more robust and generalize better [27,49,61,77,81]. Introns also do seem to provide some protection against the destructive effects of crossover and other genetic operators [1,11,49,70,72] although this may not always be helpful. The usage of explicitly defined artificial introns has yielded generally good results in linear GP [38,50,51], but in tree-based GP it usually degraded the performance of the search process [3,10,70].…”
Section: Bloatmentioning
confidence: 99%
“…Smith and Harries have shown that growth can occur in code that does influence fitness if the code has only a negligible effect on performance [14]. Soule et al have shown that code growth can also occur in exons that have a significant effect on fitness [15] [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Luke [10] has argued that introns themselves are not the cause of code growth. Smith and Harries have shown that growth can occur in code that does influence fitness (exons) if the exons only have a negligible effect on performance [17]. More recently, Soule has shown that code growth can occur even with exons that have a significant impact on the programs' fitness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nordin, Francone, and Banzhaf introduced a taxonomy of intron types for their linear GP system with 5 code categories based on whether changing the given code could affect the program's behavior [14]. Smith and Harries adopted this taxonomy for tree structured GP [17] …”
Section: Introductionmentioning
confidence: 99%